Battle Descriptions as Literary Texts
X, 372 p. 9 illus., 6 illus. in color.
Keywords: Battle descriptions are usually seen as the raw material of the military historian, who uses them to explain why generals won or lost a given battle. This volume does not aim to contribute to this discussion; it rather approaches battle descriptions as literary texts that interact with the expectations of a given audience. Therefore literary traditions in structure, vocabulary and topics of battle descriptions should be explored. The transgression of genre-borders – also literary and fictional texts are included – and a broad comparative approach, combining evidence from the third millennium BC up to the 20th century AD, makes cultural specifics and differences more easily perceivable. Contents With contributions by Marcos Such-Guttiérrez, Pavel Čech, Hilmar Klinkott, Wolfgang Oswald, Kai Ruffing, Oliver Stoll, Martin M. Bauer, Reinhold Bichler, Christian Mileta, Simon Lentzsch, Sven Günther, Dennis Pulina, JohannaLuggin, Sonjar Koroliov, Magdalena Gronau and Martin Gronau. The Editors Dr. Johanna Luggin is a post-doc researcher in the ERC-funded project “NOSCEMUS – Nova Scientia: Early Modern Science and Latin” in Innsbruck, Austria. Dr. Sebastian Fink is a postdoctoral researcher at the Academy of Finland Centre of Excellence “Changes in Sacred Texts and Traditions”.